The Influence of Intelligence on Student's Speaking Skills - Wira Kafryawan; Abdul Hakim Yassi; Nasmilah Nasmilah (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Intelligence is one of psychological factors which affect the speaking proficiency. Therefore, this study aims at finding out whether or not there is a significant correlation between students’ intelligence and their speaking skills. With regard to the methodology applied in this study, a correlation research was used to determine whether, and to what degree, a relationship exists between two or more quantifiable variables in form of quantitative method. Purposive sampling was used in the correlational research due to the assumption that the selected students were able to give information or data in relation to the research problems based on the research design. Thus, 40 students were chosen as the samples. The study was conducted at the first-year students of SMA Negeri 2 Makassar. Moreover, the quantifiable data were obtained from speaking test based on the Heaton assessment and intelligence test based on the Barret assessment which were distributed to the students. The data were then analyzed by Pearson product moment. The findings showed that there was a significant correlation between students’ intelligence and their speaking skills in degree of high correlation. In other words, the assumption views that the higher intelligence belongs to students the better ability they speak.